Enteropathogenic Escherichia coli in young Aotus (Aotidae) with diarrhea in captivity - Sánchez P., Nofre (2015)
Diarrhea is the most common sign of gastrointestinal disease in young primates kept in captivity. The study aimed to isolate and identify bacterial species present in young Aotus with diarrhoea. The animals were reared in captivity for experimental purposes. Faecal samples were collected using rectal swabs from 78 monkeys of 1 to 7 months old of A. nancymae (n=65) and A. vociferans (n=13) with diarrhoea, and 29 apparently healthy monkeys of 1 month old of A. nancymae (n=21) and A. vociferans (n=8) in the period 2002 to 2005. In the healthy group was most commonly identified E. coli, followed by Proteus vulgaris, P. mirabilis and Citrobacter freundii. A similar result was obtained in the group with diarrhea, plus Klebsiella oxytoca and Enterobacter aerogenes. Serotypes of enteropathogenic E. coli (EPEC) identified in the group with diarrhea were seven: O158, O142, O86, O125, O126, O55, and O111. The results showed that young alpacas with diarrhea have bacteria corresponding to the normal intestinal flora, and the primary isolated bacterium was E. coli.